PENGARUH KREDIBILITAS CELEBRITY ENDORSER, CITRA MEREK, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN - Faradiba, Seti Fahni; Hussein, Ananda Sabil (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2022)
In the current era of globalization, which is growing rapidly, it is the main attraction for local and foreign entrepreneurs to invest in the industrial sector, one of which is in the culinary industry in Indonesia which has an important role in economic growth in the country. This research aims to discover the effect of Celebrity Endorser’s Credibility, Brand Image, and Product Quality on Purchase Decision. The type of this research is the explanatory research which explains the relationship and influence between one variable and other through hypothesis testing. The samples of this research consist of 120 respondents. Furthermore, the respondents are the visitors and have been consume Geprek Bensu Malang City. Thus, this research uses a sampling technique with a non-probability sampling method. This research using multiple linear regression. The data were analyzed using SPSS (Statistic Product and Services Solution) for Mac version 24. The result of this research indicates that partially and simultaneously celebrity endorser’s credibility, brand image, and product quality have a significant effect on purchase decision.